Impact of Preformed Donor-Specific Anti-Human Leukocyte Antigen Antibody C1q-Binding Ability on Kidney Allograft Outcome - Molina, Juan; Navas, Ana; Agüera, María-Luisa; Rodelo-Haad, Cristian; Alonso, Corona; Rodríguez-Benot, Alberto; Aljama, Pedro; Solana, Rafael (Frontiers in Immunology, 2017)
The consolidation of single antigen beads (SAB-panIgG) assay in the detection of preformed anti-human leukocyte antigen (HLA) antibodies has improved transplantation success. However, its high sensitivity has limited the allograft allocation for sensitized patients, increasing their waiting time. A modification of the standard SAB-panIgG assay allows the detection of that subset of antibodies capable of binding C1q (SAB-C1q assay). However, the clinical usefulness of SAB-C1q assay for determining the unacceptable mismatches is under discussion. We retrospectively analyzed the impact of preformed donor-specific anti-HLA antibodies (DSA) according to the C1q-binding ability on allograft outcome, examining 389 single-kidney transplanted patients from deceased donors. Recipients with preformed C1q-binding DSA showed the lowest allograft survival up to 7 years (40.7%) compared to patients with preformed non-C1q-binding DSA (73.4%; p = 0.001) and without DSA (79.1%; p < 0.001). Allograft survival rate was similar between patients with preformed non-C1q-binding DSA and patients without preformed DSA (p = 0.403). Interestingly, among the high-mean fluorescence intensity DSA (≥10,000) population (n = 46), those patients whose DSA were further capable of binding C1q showed a poorer allograft outcome (38.4 vs. 68.9%; p = 0.041). Moreover, in our multivariate predictive model for assessing the risk of allograft loss, the presence of C1q-binding DSA (HR 4.012; CI 95% 2.326–6.919; p < 0.001) but not of non-C1q-binding DSA (HR 1.389; CI 95% 0.784–2.461; p = 0.260) remained an independent predictor after stratifying the DSA population according to the C1q-binding ability and adjusting the model for other pre-transplantation predictive factors including donor age, cold-ischemia time, and HLA-DR mismatches. In conclusion, the unacceptable mismatch definition according to the SAB-C1q assay would improve the risk stratification of allograft loss and increase the limited allograft allocation of highly sensitized patients, shortening their waiting time.